Odpowiedzi

  • Użytkownik Zadane
2009-05-17T20:57:17+02:00
F(x)=2x-3/x+1

f(x₁)=(2x₁-3)/(x₁+1)
f(x₂)=(2x₂-3)/(x₂+1)

f(x₁)-f(x₂)=(2x₁-3)/(x₁+1)-(2x₂-3)/(x₂+1)=(2x₁-3)(x₂+1) (2x₂-3)(x₁+1)
--------------- - ------------- =
(x₁+1)(x₂+1) (x₁+1)(x₂+1)

2x₁x₂+2x₁-3x₂-3 - (2x₁x₂+2x₂-3x₁-3)
------------------------------------------- =
(x₁+1)(x₂+1)

ujemne
2x₁x₂+2x₁-3x₂-3- 2x₁x₂ - 2x₂+3x₁+3 5x₁ - 5x₂ 5(x₁-x₂)
------------------------------------------- = -------------- = ---------- <0
(x₁+1)(x₂+1) (x₁+1)(x₂+1) (x₁+1)(x₂+1)
dodatnie

funkcja rosnąca